Repurposing and reshaping of hospitals during the COVID-19 outbreak in South Korea - Minyoung Her (One Health, 2020)
During the extensive outbreak of coronavirus disease 2019 (COVID-19) in South Korea, many strategies in the hospital setting, such as stratified patient care, the assignment of hospitals/beds by a task force team, and the establishment of dedicated COVID-19 hospitals, dedicated COVID-19 emergency centers, COVID-19 community facilities, and respiratory care split hospitals, were adopted to mitigate community transmission and prevent nosocomial infection. Most of these strategies were used during the Middle East Respiratory syndrome outbreak and were applied again successfully during the COVID-19 outbreak. The reallocation of health care capacity, repurposing of hospitals, and close collaboration between the government and the health care committee might have been the key to successfully addressing the crisis of COVID-19 given the shortage of health care resources.